Radiometric dating of the type-site for Homo heidelbergensis at Mauer, Germany - Wagner, Günther A.; Krbetschek, Matthias R.; Degering, Detlev; Bahain, Jean-Jacques; Shao, Qingfeng; Falguères, Christophe; Voinchet, Pierre; Dolo, Jean-Michel; Garcia, Tristan; Rightmire, G. Philip (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The Mauer mandible, holotype of Homo heidelbergensis, was found in 1907 in fluvial sands deposited by the Neckar River 10 km southeast of Heidelberg, Germany. The fossil is an important key to understanding early human occupation of Europe north of the Alps. Given the associated mammal fauna and the geological context, the find layer has been placed in the early Middle Pleistocene, but confirmatory chronometric evidence has hitherto been missing. Here we show that two independent techniques, the combined electron spin resonance/U-series method used with mammal teeth and infrared radiofluorescence applied to sand grains, date the type-site of Homo heidelbergensis at Mauer to 609 ± 40 ka. ...